Internationalization in English language courses within Languages without Borders - Silva, Nayara Stefanie Mandarino; Santos, Elaine Maria (Letras, 2022)
Internationalization has been discussed and considered an important topic to higher education. In Brazil, the lack of English proficiency perceived with the academic mobility program Science without Borders led to the creation of English without Borders, which was later amplified to Languages without Borders. In this paper, we analyze how internationalization is dealt with in LwB decrees and how the principles of the program are put to practice in its English language courses, specifically those offered at the Federal University of Sergipe. We also discuss the contributions of the program to internationalization in Brazilian universities.